Governança corporativa: um estudo de caso do banco do Brasil S/A - Souza, Pedro Donizetti de (2009)
This dissertation aims at studying the effectiveness of better practices of Corporate Governance implementation in a public company. The starting point is the premise that, making use of a responsible governance process, the inevitable conflicts between property and management will be solved, and thus, the result reflections, mainly in a public institution survival, will be preserved. The chosen company was Banco do Brasil, for its vast and turmoil two-hundred-year existence and for its recent experience with a new Corporate Governance model.